1999
DOI: 10.1177/1077727x99274004
|View full text |Cite
|
Sign up to set email alerts
|

Focus Group Discussions: Three Examples from Family and Consumer Science Research

Abstract: The purpose of this article is to demonstrate the usefulness of focus group discussions (FGDs) in family and consumer sciences research. First, we briefly describe theFGDmethodology in terms of question development, group composition and recruitment, interview protocol and logistics, and data analysis. Then, we show how we applied that methodology in three specific examples from our work with family and consumer sciences research projects. Our examples include (a) the consumer behavior of working female adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…There were three stages that we have tracked down to accomplish the FGD: questions development, grouping procedures (composition, sample selection criteria, and discussion protocol), and data analysis techniques. Along with the suggestions of Garrison et al (1999) to prepare a tool for conducting FGD, we have developed questions considering (a) the sequencing of questions from general to specific, (b) using open-ended questions instead of dichotomous questions, and (c) focusing the participants’ specific personal experiences. The first entry points were questions that gave participants an opportunity to introduce themselves and personal biographies.…”
Section: Methodsmentioning
confidence: 99%
“…There were three stages that we have tracked down to accomplish the FGD: questions development, grouping procedures (composition, sample selection criteria, and discussion protocol), and data analysis techniques. Along with the suggestions of Garrison et al (1999) to prepare a tool for conducting FGD, we have developed questions considering (a) the sequencing of questions from general to specific, (b) using open-ended questions instead of dichotomous questions, and (c) focusing the participants’ specific personal experiences. The first entry points were questions that gave participants an opportunity to introduce themselves and personal biographies.…”
Section: Methodsmentioning
confidence: 99%
“…A pool of questions was developed following Garrison et al. 's () focus group question development. Sample questions included “ Why did you choose private education programs?…”
Section: Methodsmentioning
confidence: 99%
“…The study focused on preschool because the Korean private education market has expanded recently to target preschool children (Shin, 2014), yet this segment has received limited attention in research as compared to school-age students. In addition, previous studies have found that parental involvement is greater for younger children's education than that for older children (Garrison et al, 1999). Mothers were the focus of the sample because they are the primary decision makers when it comes to children's education within Korean culture (Kim, 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While this focuses more on the narrative aspect than the research, it shows the various groups who worked together to tell these stories. Another example is a focus group study on female high school employed students and was a mutual effort between the Louisiana State University Extension Service and their Schools of Human Ecology and Forestry (Garrison et al, 1999). This project appears to be a true collaboration where faculty members from both colleges worked together on the study.…”
Section: Promoting Collaborative Researchmentioning
confidence: 99%